DEVELOPING GLOBAL BUSINESS COMMUNICATION IN ASIA a business simulated case study approach. - Lockwood, Jane; Elias, Neil ([S.l.] : ROUTLEDGE, 2021)
This book is an essential guide for anyone who wishes to develop successful business communication. It provides authentic and memorable workplace scenarios where learners become English communicators when solving authentic problems doing business together. The book aims to help learners: Use authentic workplace materials to solve problems using English Understand how language can be used as a lingua franca effectively when communicating Understand how intertextuality between shared spoken and written texts drives communication Improve communicative performance in spoken and written texts Become familiar with the communication realities of workplaces that are becoming increasingly technology driven and globalised This book will help learners become better equipped with communication strategies through its real life applicable and skills-based examples and will be a useful reference in the digital age.
OCLC-licensed vendor bibliographic record.
Keywords: Communication in organizations -- Asia; Intercultural communication -- Asia; BUSINESS & ECONOMICS / General